Proteomics Analysis Reveals Stable Multiprotein Complexes in Both Fission and Budding Yeasts Containing Myb-Related Cdc5p/Cef1p, Novel Pre-mRNA Splicing Factors, and snRNAs - Ohi, Melanie D. (American Society for Microbiology, 2002)
Schizosaccharomyces pombe Cdc5p and its Saccharomyces cerevisiae ortholog, Cef1p, are essential Myb-related proteins implicated in pre-mRNA splicing and contained within large multiprotein complexes. Here we describe the tandem affinity purification (TAP) of Cdc5p- and Cef1p-associated complexes. Using transmission electron microscopy, we show that the purified Cdc5p complex is a discrete structure. The components of the S. pombe Cdc5p/S. cerevisiae Cef1p complexes (termed Cwfs or Cwcs, respectively) were identified using direct analysis of large protein complex (DALPC) mass spectrometry (A. J. Link et al., Nat. Biotechnol. 17:676-682, 1999). At least 26 proteins were detected in the Cdc5p/Cef1p complexes. Comparison of the polypeptides identified by S. pombe Cdc5p purification with those identified by S. cerevisiae Cef1p purification indicates that these two yeast complexes are nearly identical in composition. The majority of S. pombe Cwf proteins and S. cerevisiae Cwc proteins are known pre-mRNA splicing factors including core Sm and U2 and U5 snRNP components. In addition, the complex contains the U2, U5, and U6 snRNAs. Previously uncharacterized proteins were also identified, and we provide evidence that several of these novel factors are involved in pre-mRNA splicing. Our data represent the first comprehensive analysis of CDC5-associated proteins in yeasts, describe a discrete highly conserved complex containing novel pre-mRNA splicing factors, and demonstrate the power of DALPC for identification of components in multiprotein complexes.